Relationship between blood pressure levels during thrombolytic therapy and functional outcomes in patients with middle cerebral artery infarction - Güneş, Muzaffer (Journal of Surgery and Medicine, 2020)
Aim: Previous studies have investigated the relationship between blood pressure (BP) level before and after intravenous (IV) thrombolytic therapy, and functional outcomes of acute ischemic stroke (AIS). However, the relationship between BP level during thrombolytic infusion and functional outcomes has not been well studied. Therefore, in this study, we investigated the relationship between BP levels during thrombolytic therapy and functional outcomes at the 3rd month in AIS patients with middle cerebral artery (MCA) infarction. Methods: This case-control study was conducted on 60 patients with infarcts in more than 1/3 of MCA. Among these, 20 patients underwent IV thrombolytic therapy after giving informed consent (study group). Forty patients who did not receive thrombolytic therapy were included in the control group. Patients undergoing IV thrombolytic therapy were divided into two groups according to modified Rankin Scale (mRS) at the 3rd month: Those with good functional outcomes (mRS score=0–2) and poor functional outcome (mRS score=3–6). Results: The poor functional outcome group had a higher mean diastolic BP than the good functional outcome group (P=0.01). Systolic BP was <140 mmHg and diastolic BP was <75 mmHg in the good functional outcome group. A significant, positive, and moderate correlation was found between the mRS score and diastolic BP at the time of admission to the emergency department (r=0.679, P=0.001), immediately before (r=0.580, P=0.007), and during IV thrombolytic therapy (r=0.643, P=0.002). Conclusion: In AIS patients with MCA infarction, high diastolic BP levels during IV thrombolytic therapy are associated with poor functional outcomes.